QTc Time Correlates with Amitriptyline and Venlafaxine Serum Levels in Elderly Psychiatric Inpatients - Hefner, Gudrun; Hahn, Martina; Hohner, Matthias; Roll, Sybille C.; Klimke, Ansgar; Hiemke, Christoph (Pharmacopsychiatry, 2019)
Introduction Many antidepressants cause QT prolongation but the classification of cardiac risk of these drugs varies markedly in different published lists. This retrospective study analyzed the correlation of QTc time with amitriptyline and venlafaxine serum level in elderly psychiatric inpatients.Methods Elderly inpatients aged≥65 years for whom venlafaxine or amitriptyline serum level had been measured were selected retrospectively from a therapeutic drug monitoring database and screened for an electrocardiogram measurement at the time of blood withdrawal. The correlation of amitriptyline or venlafaxine serum levels with QTc time was examined by using Pearson’s correlation analysis.Results Amitriptyline serum levels (n=11) correlated significantly with QTc time (r=0.918, p<0.001, CI 95%). Venlafaxine serum levels (n=27) also correlated significantly with QTc time (r=0.382, p<0.05, CI 95%).Discussion Amitriptyline and venlafaxine induce QT prolongation depending on drug concentrations in blood. Its extent, however, is very low when drug serum levels are within the therapeutic range. Future pharmacokinetic studies that correlate drug serum level and QT time should classify the cardiac risk of drugs based on the grade of the regression line in relation to the therapeutic range.
Keywords: amitriptyline; venlafaxine; serum level; QT prolongation; therapeutic drug monitoring